Legal Analysis of Patient and Family Consent as a Form of Agreement in the Implementation of Medical Procedures in Hospitals - Muhammad Purnomo; Rusnoto Rusnoto; Achmad Jumeri Pamungkas (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
Patient and family decision-making regarding medical procedures is a crucial process in health care that requires conscious and voluntary consent, known asinformed consentThis process is influenced by various multidimensional factors that are not yet fully understood, especially in private hospitals in Central Java. Objective:This study aims to identify and analyze factors that influence patient and/or family decision-making regarding medical procedures performed by doctors. Method: This quantitative research uses an approachanalytical descriptivewith designcross-sectional.A sample of 120 respondents was selected using the techniquepurposive samplingfrom six private hospitals in Kudus, Demak, and Jepara Regencies. Data were collected using a structured questionnaire that had been tested for validity and reliability, and analyzed using a multivariate analysis.Pearson Correlation And simple linear regression. Results:There is a significant relationship between knowledge (r=0.304; p=0.001), psychological (r=0.323; p=0.001), cultural-religious (r=0.336; p=0.001), economic conditions (r=0.925; p=0.001), and trust in medical personnel (r=0.334; p=0.001) factors with medical decision-making. Multivariate analysis shows thateconomic conditionsis the most dominant factor influencing patient decisions (R²=0.864; p=0.001).Conclusion:Patient and family decision-making regarding medical procedures is influenced by various factors, primarily economic conditions, followed by cultural-religious and psychological aspects. Interventions that strengthen psychological support, are sensitive to cultural values, and improve financial access are key to improving the process.informed consentwhich is more effective.